(untitled) (Voice of Teacher, 2021)
This article aims to describe undergraduate-level female students’ motivation, interest, and perceived self-efficacy in mathematics. This is a cross-sectional descriptive study. All 84 female students who were studying mathematics at the undergraduate level in the selected nine different campuses of Tribhuvan University (TU) of Kathmandu valley and one campus of Kathmandu University (KU) were included as a sample of the study. Data were collected from sample female students through a self-administered questionnaire. Female students were found to be motivated and encouraged by their parents and teachers to study mathematics at undergraduate level. Fifty-two percent of respondents were confident in obtaining A grade in mathematics but most of them have a moderate level of self-efficacy to learn mathematics concepts and theories. Self-efficacy belief is significantly higher among daughters of educated mothers (above high school) (79%) compared to daughters of mothers with high school education and below (43%). Perceived self-efficacy of the female students is influenced by various factors including the educational status of parents, family support, and teachers’ encouragement. Association between parents’ education and self-efficacy is found significant at p-value < 0.05. It can be said that parents’ education and teachers’ encouragement influence the mathematical self-efficacy of female students to some extent.